MYSTICISM: THE DEPTH-DIMENSION OF SPIRITUALITY - Painadath, Sebastian (Journal of Dharma, 2005)
The word mysticism is derived from the Greek verb muein, which means to hide, to conceal, or to close the eyes. The word mystery too comes from the same verb. Mysticism is, therefore, basically sensitivity to the mystery of being. A mystic is gripped by an intense awareness of the mystery of the noumenon behind the phenomenon. The search takes the seeker from the visible to the invisible, from form to the formless, from multiplicity to unity, from diversity to the One (to hon, ekam). Ultimately, it is a search for the Beyond, for the Absolute, for the unifying power: for the ôta, for the Tao, for the Brahman, for the Dhamma, for the Divine. The unfathomability and incomprehensibility of the Divine is the horizon of any authentic mystical experience. Hence, the mystic draws life from contemplative silence before the abysmal depth of God.